Clay Workshop as Staff's Competency Self-Evaluation Related to Business Strategy - Riitta Forsten-Astikainen; Kyllikki Taipale-Erävala (International School for Social and Business Studies, 2018)
This case study examines staff members' self-evaluations of competency relative to a set business strategy and firm's strategic goals. The study employed a rarely utilized arts-based research approach focused on a clay workshop in conjunction with storytelling. The data was collected via interviews with 16 staff members participating in strategy discussions. The research demonstrated that the inclusion of staff members in a firm's strategy efforts can produce more diversity and greater creativity by increasing the utilization of reflection as a strategic method. The originality of this study lies in the methodology: a clay-centered workshop was utilized to produce staff's reflections.